New studies in Deweyan education democracy and education revisited - Kricke, Meike 1982-; Neubert, Stefan (Routledge, 2020)
"This book examines in detail some of John Dewey's most influential writings by connecting them with contemporary issues, perspectives, controversies and debates. Bringing together scholars from the US and Germany, this volume offers an international perspective on current implications, challenges, and risks of democracy and education in the contemporary world. Written for students and scholars in the fields of education and philosophy, New Studies in Deweyan Education, represents a new, unique and innovative way to of approaching the problems and opportunities of democracy and education then and now"--
Description based on online resource; title from digital title page (viewed on April 20, 2020)
Keywords: Dewey, John / 1859-1952 / Influence; Education / Philosophy; Democracy and education